2018
DOI: 10.1073/pnas.1803989115
|View full text |Cite
|
Sign up to set email alerts
|

Divergent drivers of leaf trait variation within species, among species, and among functional groups

Abstract: SignificanceLeaf traits, such as photosynthetic capacity, nitrogen concentration, and leaf mass per area, strongly affect plant growth and nutrient cycles. Understanding relationships among leaf traits is, therefore, a fundamental challenge in plant biology, crop science, and ecology. Different groups of leaves exhibit distinct relationships among pairs of traits. For example, photosynthetic capacity per unit leaf area increases strongly with leaf mass per area from sun to shade within species, but these same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
137
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(142 citation statements)
references
References 47 publications
4
137
0
1
Order By: Relevance
“…In vascular plants, experimental studies have shown a positive correlation between stomatal conductance and photosynthetic rates (Tanaka et al 2013, Lawson andBlatt 2014). The leaf masscarbon economic spectrum was defined by variation from high to low specific leaf area (and low to high leaf thickness), which is associated with a gradient of investment in structural components and rates of carbon assimilation (Wright et al 2004, Osnas et al 2018). The leaf masscarbon economic spectrum was defined by variation from high to low specific leaf area (and low to high leaf thickness), which is associated with a gradient of investment in structural components and rates of carbon assimilation (Wright et al 2004, Osnas et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vascular plants, experimental studies have shown a positive correlation between stomatal conductance and photosynthetic rates (Tanaka et al 2013, Lawson andBlatt 2014). The leaf masscarbon economic spectrum was defined by variation from high to low specific leaf area (and low to high leaf thickness), which is associated with a gradient of investment in structural components and rates of carbon assimilation (Wright et al 2004, Osnas et al 2018). The leaf masscarbon economic spectrum was defined by variation from high to low specific leaf area (and low to high leaf thickness), which is associated with a gradient of investment in structural components and rates of carbon assimilation (Wright et al 2004, Osnas et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, communities in the hot lowlands were comprised of species with larger leaves, possibly because of a higher investment by plants in metabolically active tissues that enhance photosynthetic capacity (Osnas et al 2018). For example, communities in the hot lowlands were comprised of species with larger leaves, possibly because of a higher investment by plants in metabolically active tissues that enhance photosynthetic capacity (Osnas et al 2018).…”
Section: The Macroclimatic Effects On the Elevational Patterns Of Epimentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. ) is consistent with a conceptual framework contrasting mass‐proportional and area‐proportional investments (Osnas et al ., , ; Katabuchi et al ., ). With the exception of P mass , the allometric scaling of variation in response to resource availability in the suite of LES traits is significantly linked to LMA, including P area .…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers on modes of trait expression (Osnas et al ., , ; Katabuchi et al ., ) offer novel insights into the traditional view that species with a greater LMA tend to have longer‐lived leaves in compensation for their lower photosynthetic capacity (Wright et al ., ). Osnas et al .…”
Section: Introductionmentioning
confidence: 99%